2018
DOI: 10.2174/1389201019666180620111025
|View full text |Cite
|
Sign up to set email alerts
|

Snake Venom, A Natural Library of New Potential Therapeutic Molecules: Challenges and Current Perspectives

Abstract: It is believed that significant experimental and computational advances will arise in similar proportions in the coming years that will allow researchers to map the molecular regions responsible for their pharmacological actions, their respective mechanisms of action and their cell targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Genomic and transcriptomic studies have proved to be an invaluable tool in the discovery of the snake venom evolution and proteoform [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Consequently, investigations are directed towards the discovery of pharmacologically active snake venom compounds [ 35 , 36 , 37 , 38 ]. For example, a recent study reported Mambaquaretin-1 (peptide from green mamba venom), as a promising candidate for the treatment of polycystic kidney disease [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genomic and transcriptomic studies have proved to be an invaluable tool in the discovery of the snake venom evolution and proteoform [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Consequently, investigations are directed towards the discovery of pharmacologically active snake venom compounds [ 35 , 36 , 37 , 38 ]. For example, a recent study reported Mambaquaretin-1 (peptide from green mamba venom), as a promising candidate for the treatment of polycystic kidney disease [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, molecules of animal origin have stood out in the scientific literature for presenting microbicidal properties and within this group, snake venoms have been the target of numerous studies ( Harvey et al, 1998 ; Koh et al, 2006 ). Snake venoms are characterized by the complex constitution of molecules, mainly of a protein nature, which are related to a wide spectrum of pharmacological effects ( Lomonte et al, 2014 ; Simoes-Silva et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, various bioactive proteins and peptides have been reported from the venom of different species of snakes, conus, scorpions, centipedes, lizards, spiders, sea anemones, bees and octopus [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. In this context, venomous snakes are a focus of investigations, and a large number of pharmacologically useful molecules have already been isolated and characterized from snake venoms [ 10 , 11 ]. Among the approximately 3000 known snake species, only a relatively small number are venomous, mainly belonging to Viperidae and Elapidae families.…”
Section: Introductionmentioning
confidence: 99%